Death under the dryer : [large type] : a Fethering mystery - Brett, Simon (Brett, Simon. Fethering mysteries., 2007)
When Carole goes for a hair trim at Connies Clip Joint, she doesnt expect to find herself at the scene of a murder. But sure enough in the backroom, strangled by the cord of a hairdryer, sits Connies young assistant, Kyra. Whilst Carole and her sleuthing friend Jude enjoy some tactical snooping, Fethering fingers are pointing firmly at Kyras boyfriend, Nathan, who has disappeared. But Nathans family are also acting rather oddlywhilst convinced of Nathans innocence, they dont seem so certain that he is actually missing. Meanwhile Connies ex-husband Martin, co-owner of the rival hairdressing chain Martin & Martina, appears to have been quite the ladies man with his young assistants, including Kyra herself. Could he have silenced her before she divulged his sordid secret and potentially ruined his career? As our discreet lady detectives decide there are only so many haircuts they can have for the sake of neighbourhood crime solving, so too do they realise this is no cut and dry case, and that some people will stop at nothing to keep their private lives concealed